1996
DOI: 10.1016/0014-5793(96)00382-1
|View full text |Cite
|
Sign up to set email alerts
|

Shortcut of the photosynthetic electron transfer in a mutant lacking the reaction center‐bound cytochrome subunit by gene disruption in a purple bacterium, Rubrivivax gelatinosus

Abstract: A mutant lacking the reaction center-bound cytochrome subunit was constructed in a purple photosynthetic bacterium, Rubrivivax gelatinosus IL144, by inactivation of the cytochrome gene. Photosynthetic growth of the C244 mutant strain occurred at approximately half the rate of the wild-type strain. Although mutagenesis resulted in a greatly reduced amount of memhrane-bound cytochromes c, illumination induced cyclic electron transfer and the generation of membrane potential in the mutant as observed in the wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…We have previously reported that a R. gelatinosus mutant lacking the cytochrome subunit is able to grow photosynthetically (43). Possibly, the main role of the cytochrome subunit is to reduce the photo-oxidized special pair of bacteriochlorophyll fast enough to avoid the electron backflow ("back reaction") from the ubiquinone to the oxidized special pair.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that a R. gelatinosus mutant lacking the cytochrome subunit is able to grow photosynthetically (43). Possibly, the main role of the cytochrome subunit is to reduce the photo-oxidized special pair of bacteriochlorophyll fast enough to avoid the electron backflow ("back reaction") from the ubiquinone to the oxidized special pair.…”
Section: Discussionmentioning
confidence: 99%
“…Rvi. gelatinosus strains were grown in a rotary shaker in the dark at 30°C in PYS medium (43). Microoxic and oxic growth regimes were achieved as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…Rvi. gelatinosus was transformed using a method described by Nagashima et al (43). Sequences of primers used in this study are listed in Table S3.…”
Section: Construction Of Mutantsmentioning
confidence: 99%
“…palustris strain Rits from our culture collection and Rhodobacter (Rba.) sphaeroides 2.4.1 were grown on agar plate of PYS medium [10], and each single clone was used for this study. These bacteria were cultured anaerobically at 30°C with a usual light intensity of 30 lE m À2 s À1 in the liquid PYS medium.…”
Section: Culturing Of Purple Photosynthetic Bacteriamentioning
confidence: 99%